Advances in liquid crystals. - Brown, Glenn Halstead (Elsevier Science : Academic Press, 1979)
Advances in Liquid Crystals, Volume 4 is a collection of papers that deals with liquid crystal sciences, particularly the flow problems in liquid crystals, the effects of high pressure on liquid crystals, lyotropic and thermotropic polymeric liquid crystals, and the light-scattering properties of thermotropic liquid crystals. One paper reviews the continuum theory in flow problems in liquid crystals, presents theoretical predictions, and compares these with associated observations. High-pressure experiments in liquid crystals pave the way for discoveries involving pressure-induced mesomorphis.